Needs of Families with a Member with Neuromuscular Pathology: Functional Dimension - Marques, Tiago (2023)
Background: meeting the needs of families with a member who has a Neuromuscular Disorder (ND), enables an improvement in their quality of life, minimizing the possibility of illness and allowing greater family contribution to their functions. Objectives: characterize the needs of families with a member who has a ND in the functional dimension. Methodology: a quantitative, descriptive, cross-sectional study was carried out with an intentional sample of 30 families. The operative matrix of the Dynamic Model of Family Assessment and Intervention (MDAIF) was used as a data collection instrument. Data processing and analysis were performed by descriptive statistics. Results: most members who have a ND are dependent on self-care, clothing, hygiene and using the bathroom; families have saturation of home care role and caregiver role. Conclusion: family nurses will be able to help families by creating programs that allow: -the readjustment of family roles where there is saturation; -the possibility of working and supporting caregivers; -specific training regarding the people who have a ND.